Estimating the Water Budget of the Upper Blue Nile River Basin With Water and Energy Processes (WEP) Model - Abebe, Sintayehu A.; Qin, Tianling; Zhang, Xin; Li, Chenhao; Yan, Denghua (Frontiers in Earth Science, 2022)
Understanding the spatial and temporal distributions and variations of basin water budget components is essential for effective water resources management. Due to a lack of basic hydro-meteorological information, the Upper Blue Nile River Basin (UBNRB) remains poorly understood in quantifying its hydrologic fluxes and associated dynamics. This study used a physically based distributed hydrologic model, WEP. We used multi-year land use information to better estimate the water budget components (evapotranspiration, runoff and storage) of the UBNRB. WEP simulation was validated at two main sections of the Upper Blue Nile river monthly from 1992 to 2014 (23 years). Results show that the basin stores a significant amount of water during the long rainy season (June to September) due to higher precipitation and limited evapotranspiration. However, it loses this storage through evapotranspiration during the dry season (October to February). The overall basin precipitation is 1051 mm per year. Evapotranspiration accounts for 58% of the annual water budget, runoff is 25% and storage is 18%. The findings reported in this study can shed some light on understanding the UBNRB water budget dynamics and inform water management practitioners.